PENGARUH FEAR OF MISSING OUT (FOMO) TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE DENGAN KONTEN MEDIA SOSIAL TIKTOK SEBAGAI VARIABEL MODERASI - Fitri Fauziah; Netti Nurlenawati; Dexi Triadinda (POLITEKNIK LP3I JAKARTA, 2025)
Technological advances make it easier for people to access various information, in terms of shopping, including in the increasingly growing skincare industry. One of the elements that influences consumer behavior in making skincare purchases is the Fear of Missing Out (FoMo) which triggers the fear of missing the opportunity to get the latest products or follow popular trends. Through user reviews, influencer recommendations, and product reviews, social media contributes significantly to the rapid spread of information about skincare products. By using social media content as a moderating variable, this study tries to find out how FoMo influences the purchase of skincare products. The methodology of this study is a quantitative approach that combines a purposive sampling approach on social media users who also use skincare products. Determination of the number of samples using the Hair formula which produces 100 respondents. The collected data was transformed using MSI then analyzed using the classical assumption test and moderation regression with the SPSS analysis tool. The study findings show that social media and FoMo content influence consumer decisions to purchase significantly and positively, and the interaction between FoMo and social media content has a negative effect although it remains significant. Overall, FoMo and social media content have been shown to influence consumer purchasing decisions.